Acute Kidney Injury Treated with Dialysis outside the Intensive Care Unit: A Retrospective Observational Single-Center Study - Sprenger-Mähr, Hannelore (PLoS One, 2016)
INTRODUCTION: The number of patients suffering from acute kidney injury requiring dialysis (AKI-D) is increasing. Whereas causes and outcome of AKI-D in the intensive care unit (ICU) are described extensively, few data exist about AKI-D patients treated outside the ICU. Aim of this study was to identify the causes of AKI-D, determine in-depth the comorbid conditions and outcome of this particular patient group and identify possibilities for its prevention. METHODS: We retrospectively studied all AKI-D patients treated outside the ICU in a single nephrology referral center between January 2010 and June 2015. Data on comorbid conditions, renal function and drug therapy prior to AKI-D, and possible causal events were collected. Patients were grouped into those with renal hypoperfusion as the predominant cause of AKI-D (hemodynamic group) and those with other causes (non-hemodynamic group). RESULTS: During 66 months 128 patients (57% male, mean age 69.3 years) were treated. AKI-D was community-acquired in 70.3%. The most frequent comorbidities were hypertension (62.5%), chronic kidney disease (CKD) (58.9%), coronary artery disease (CAD) (46.1%), diabetes (35.9%) and heart failure (34.1%). Most patients were prescribed diuretics (61.7%) and inhibitors of the renin-angiotensin-aldosterone system (RASI) (57.8%); 46.1% had a combination of both. In the 88 patients with hemodynamic AKI-D (68.8%) the most frequent initiating events were diarrhea (39.8%), infections (17.0%) and acute heart failure (13.6%). In the 40 patients with non-hemodynamic AKI-D (31.2%) interstitial nephritis (n = 15) was the prominent diagnosis. Patients with hemodynamic AKI-D were older (72.6 vs. 62.1 years, p = 0.001), suffered more often from CKD (68.2% vs. 33.3%, p = 0.003), CAD (54.5% vs. 27.5%, p = 0.004) and diabetes (42.0% vs. 22.5%, p = 0.033), and were more frequently on diuretics (75.0% vs. 32.5%, p<0.001), RASI (67.0% vs. 37.5%, p = 0.002) or their combination (58.0% vs. 20.0%, p<0.001). Twenty-two (17.2%) patients died and 27 (21.1%) patients died or developed end-stage renal disease. CONCLUSION: AKI-D treated outside the ICU is most often caused by renal hypoperfusion. It predominantly afflicts elderly patients with one or more comorbid conditions, who are treated with diuretics and RASI and have an acute illness leading to volume depletion. Early discontinuation of these drugs may be a successful strategy to avoid AKI-D in vulnerable patients.